“I Didn't See It as a Problem, I Thought It Was Going to Be Taken Away”: Narratives From Family Members of Users in Rehab - Almanza-Avendaño, Ariagor Manuel; Romero Mendoza, Martha; Gomez-San Luis, Anel Hortensia (Frontiers in Psychiatry, 2021)
Multiple discourses on addictions influence the way relatives interpret the substance use of a family member. The purpose of this study is to understand the influence of these discourses on the construction of use as a problem by relatives of people in recovery. Narratives were obtained on the path of the illness to identify the phases in the construction of use as a problem and the influence of the discourses on each phase. The process has four successive phases: normalization, impasse, exasperation and adoption of the treatment ideology. This process goes from the legitimization of use to its moral interpretation and subsequently to the transition to medical discourse. It is concluding that it is important to reduce the influence of moral discourse in order to facilitate timely detection and early care, as well as to design interventions focused on the reconstruction of use as a problem.